2005
DOI: 10.1103/physrevb.72.024115
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the colossal dielectric response ofPr0.6Ca0.4MnO3

Abstract: We report the detailed study of dielectric response of Pr0.6Ca0.4MnO3 (PCMO), member of manganite family showing colossal magnetoresistance. Measurements have been performed on four polycrystalline samples and four single crystals, allowing us to compare and extract the essence of dielectric response in the material. High frequency dielectric function is found to be ε0=30, as expected for the perovskite material. Dielectric relaxation is found in frequency window of 20Hz-1MHz at temperatures of 50-200K that yi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
66
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 28 publications
6
66
1
Order By: Relevance
“…If the dielectric is not a very good insulator, this can cause the electric field to be mostly dropped in the charge-depleted interfacial area rather than in the core of the material, yielding artificially high apparent dielectric constants. This effect has been documented in several oxide materials, including manganites, [20][21][22] and may happen not only at dielectricelectrode interfaces but also at grain boundaries in ceramics 23 and interslab interfaces in superlattices. 24 Whether the heterogeneous nature of the sample is accidental ͑interfacial or grain-boundary layers͒, or deliberate ͑superlattices͒, either case can be described by the MaxwellWagner ͑M-W͒ capacitor model.…”
mentioning
confidence: 99%
“…If the dielectric is not a very good insulator, this can cause the electric field to be mostly dropped in the charge-depleted interfacial area rather than in the core of the material, yielding artificially high apparent dielectric constants. This effect has been documented in several oxide materials, including manganites, [20][21][22] and may happen not only at dielectricelectrode interfaces but also at grain boundaries in ceramics 23 and interslab interfaces in superlattices. 24 Whether the heterogeneous nature of the sample is accidental ͑interfacial or grain-boundary layers͒, or deliberate ͑superlattices͒, either case can be described by the MaxwellWagner ͑M-W͒ capacitor model.…”
mentioning
confidence: 99%
“…It is worth noting that the magnitude of presented dielectric constants without magnetic field is comparable with the bulk bismuth titanate in single crystals and polycrystals [18]. Therefore it is reasonable to exclude the extrinsic contributions from the Schottky barriers at electrical contacts [19]. Experiments showed that there was a magnetic transition from antiferromagnetism (AFM) to weak ferromagnetism at 65K for bulk Bi 6 Fe 2 Ti 3 O 18 materials [8].…”
Section: Resultsmentioning
confidence: 99%
“…There is a report in the literature for the occurrence of a dielectric anomaly in Pr 0.6 Ca 0.4 MnO 3 around the charge-ordering transition temperature [11]. Although magnetic fields are noted to affect the dielectric properties of the manganites [12], there has been no definitive study of the effect of magnetic fields on the dielectric properties to establish whether there is coupling between the electrical and magnetic order parameters.…”
mentioning
confidence: 99%